2010
DOI: 10.1093/carcin/bgq098
|View full text |Cite
|
Sign up to set email alerts
|

Apc MIN modulation of vitamin D secosteroid growth control

Abstract: A central paradox of vitamin D biology is that 1alpha,25-(OH)(2) D(3) exposure inversely relates to colorectal cancer (CRC) risk despite a capacity for activation of both pro- and anti-oncogenic mediators including osteopontin (OPN)/CD44 and E-cadherin, respectively. Most sporadic CRCs arise from adenomatous polyposis coli (APC) gene mutation but understanding of its effects on vitamin D growth control is limited. Here we investigate effects of the Apc(Min/+) genotype on 1alpha,25-(OH)(2) D(3) regulation of OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 67 publications
4
26
0
Order By: Relevance
“…Because CD44 is a main receptor for several key extracellular matrix proteins such as osteopontin and hyaluronan (Ponta et al, 2003), the repression of CD44 by 1␣,25(OH) 2 D 3 and its analogs may contribute to their anticancer activities. A recent colon cancer study demonstrated that 1␣,25(OH) 2 D 3 or its analogs increased the expression of osteopontin, but they suppressed the expression of CD44 and enhanced the expression of E-cadherin, which may contribute to their inhibitory effect on adenoma formation in APC Min/ϩ mice (Xu et al, 2010). In the present study, BXL0124 decreased the expression of CD44 mRNA and protein (Figs.…”
Section: Discussionsupporting
confidence: 53%
“…Because CD44 is a main receptor for several key extracellular matrix proteins such as osteopontin and hyaluronan (Ponta et al, 2003), the repression of CD44 by 1␣,25(OH) 2 D 3 and its analogs may contribute to their anticancer activities. A recent colon cancer study demonstrated that 1␣,25(OH) 2 D 3 or its analogs increased the expression of osteopontin, but they suppressed the expression of CD44 and enhanced the expression of E-cadherin, which may contribute to their inhibitory effect on adenoma formation in APC Min/ϩ mice (Xu et al, 2010). In the present study, BXL0124 decreased the expression of CD44 mRNA and protein (Figs.…”
Section: Discussionsupporting
confidence: 53%
“…Consistent with this hypothesis, Xu et al (2010) have demonstrated that administration of 1,25(OH) 2 D 3 or that of its analogues for 12 weeks reduces the number of polyps in the colon mucosa and that, in the small intestine and in the colon, this effect is associated with a reduced expression of target genes for b-catenin. The effects mediated by Vit D may also indirectly affect the function of b-catenin through an increased production of E-cadherin, a membrane protein that binds b-catenin, thus preventing its nuclear localization and transactivation (Pálmer et al, 2001).…”
Section: Vit D Interaction With Wnt/b-catenin-signaling Pathwaysmentioning
confidence: 66%
“…These effects are suppressed upon diet supplementation with calcium and vitamin D (reviewed in Lamprecht & Lipkin (2003) (Huerta et al 2002), a mouse model of intestinal carcinogenesis that carries a mutated allele of the tumour suppressor gene Apc and spontaneously develops multiple neoplasias throughout the intestinal tract (Su et al 1992). Xu et al (2010) confirmed these results and also found that treatment with 1,25(OH) 2 D 3 or two of its analogues increases the expression of E-cadherin, inhibits that of Myc and reduces b-catenin nuclear levels in the small intestine and colon of Apc min/C mice. However, a recent study by Irving et al (2011) has shown that treatment with 25(OH)D 3 or two 1,25(OH) 2 D 3 analogues did not affect intestinal tumour development in the Apc Pirc/C rat or in the Apc min/C mouse models in the absence or presence of the colonic tumour inducer dextran sodium sulphate.…”
Section: Anti-tumoural Action Of Vitamin D In Animal Models Of Crcmentioning
confidence: 99%